Manajemen Pembelajaran Bahasa Arab di SMP Qur’an Darul Fattah (SQDF) Bandar Lampung - Fitriani, Fitriani; Akmansyah, Muhammad; Basyori, Ahmad; Erlina, Erlina; Koderi, Koderi (CV. Creative Tugu Pena, 2023)
Learning Arabic has several indicators that must be met, namely Planning, Implementation and Evaluation of Learning. The purpose of these three stages is so that every student in the class can study in an orderly manner so that the learning objectives are achieved effectively and efficiently. The method used in this research is Field Research and the nature of the research is qualitative descriptive, and uses primary and secondary data sources obtained from library research and field studies, while the data collection method uses the Observation method which is carried out when the implementation and evaluation of learning takes place, Interview conducted by researchers to teachers, principals and students, and documentation in the form of documents related to lesson plans, student scores and evaluation tools. Data analysis using qualitative analysis. The results of the study show that learning Arabic at SMP Qur'an Darul Fattah at the Planning stage is carried out by making a Curriculum and Masterplan design, then the implementation is carried out using 4 methods and in using media, the media used is PowerPoint media then at the Evaluation Stage it is carried out with Two Models Evaluation, namely the model of oral tests and written tests with 4 aspects of basic competency standards that must be mastered as well as for assessment standards, namely 35, and if there are students who have not met this number, remedial will be carried out to achieve assessment standards.